Permodelan Faktor Produksi pada Usaha Kecil Menengah (Studi kasus di UKM Harapan Nunggal, Jakarta) - Yashinta Triwulandari; Peni Sawitri (Universitas Negeri Surabaya, 2018)
AbstractGetting a big advantage is the main goal in every business. To that end, the company will be required to produce products with the use of maximum resources to provide optimal benefits. Companies must also consider any changes that occur, either from profits or resources optimally so as not to affect corporate profits. This study aims to know the size of optimal benefits for the utilization of resources for the production tofu that can be obtained by SMEs Harapan Nunggal simplex method, and knowing that changes can still be tolerated without altering the optimal gains obtained. With the assumption of tofu as a product is inelastic, because the price changes that occur will not affect to demand of tofu. The results of this study and based on the calculation of the simplex method, optimal benefit is obtained when SMEs Harapan Nunggal produce small tofu as much as 14.595 pieces. The amount of maximum profit is Rp. 729.729,8,- for each production activity/ day. And changes can still be tolerated without altering Optimization profits is to do the appropriate changes or are in the range of feasibility in sensitivity analysis.